IL-1/TNF-α Inflammatory and Anti-Inflammatory Synchronization Affects Gingival Stem/Progenitor Cells’ Regenerative Attributes - Fan Zhang; Misi Si; Huiming Wang; Mohamed K. Mekhemar; Christof E. Dörfer; Karim M. Fawzy El-Sayed (Stem Cells International)
Cytokines play major roles in tissue destruction/repair. The present study investigates proliferative and osteogenic differentiation potentials of gingival mesenchymal stem/progenitor cells (G-MSCs), influenced by IL-1/TNF-α inflammatory/anti-inflammatory conditions. Human G-MSCs were isolated, characterized, and cultured in basic medium (control group, M1), in basic medium with IL-1β, TNF-α, and IFN-γ (inflammatory group, M2) and with IL-1ra/TNF-αi added to M2 (anti-inflammatory group, M3). MTT tests at days 1, 3, and 7 and CFU assay at day 12 were conducted. Osteogenic differentiation was analyzed by bone-specific transcription factors (RUNX2), alkaline phosphatase (ALP), type I collagen (Col-I), osteopontin (OPN), and osteonectin (ON) expression at days 1, 3, 7, and 14 and Alizarin red staining at day 14. At day 3, the control group showed the highest cell numbers. At day 7, cell numbers in inflammatory and anti-inflammatory group outnumbered the control group. At day 12, CFUs decreased in the inflammatory and anti-inflammatory groups, with altered cellular morphology. The anti-inflammatory group demonstrated elevated bone-specific transcription factors at 14 days. After 14 days of osteogenic induction, calcified nodules in the anti-inflammatory group were higher compared to control and inflammatory groups. For regeneration, initial inflammatory stimuli appear essential for G-MSCs’ proliferation. With inflammatory persistence, this positive effect perishes and is followed by a short-term stimulatory one on osteogenesis. At this stage, selective anti-inflammatory intervention could boost G-MSCs’ differentiation.